Micronutrient Density and Stability in West African Pearl Millet—Potential for Biofortification. Issue 4 (1st July 2014) - Pucher, Anna; Høgh‐Jensen, Henning; Gondah, Jadah; Hash, C. Tom; Haussmann, Bettina I. G.
ABSTRACT: Pearl millet [ Pennisetum glaucum (L.) R. Br.] is one of the most important cereals in West and Central Africa (WCA). Human populations in WCA are strongly affected by micronutrient deficiencies. Biofortification, the development of pearl millet varieties with enhanced micronutrient levels, is recognized as a suitable approach to reducing this widespread health problem. To assess the potential of biofortification of WCA pearl millet germplasm, we studied quantitative‐genetic parameters of eight mineral densities in whole and decorticated grains, their stability over environments, and the correlations among minerals and agromorphological traits. The study included 72 WCA pearl millet genotypes grown in three environments in Niger, contrasting in soil fertilization. Significant genotypic effects, moderate estimates of heritability, and genetic variation for mineral densities, especially for Fe and Zn, indicate a high potential for biofortification of WCA pearl millet. However, screening of additional landraces or introgression of favorable alleles from highly nutrient‐dense Indian germplasm could expedite achievement of higher densities. Genotype‐by‐environment interaction effects were significant for Fe and Zn grain densities, showing the importance of multienvironmental evaluation for identifying stable genotypes. Identified genotypes with relatively stable Fe and Zn grain densities appear suitable for use in future WCA pearl millet biofortification breeding programs.